Sustainable Development Goals (SDGS) dan Indonesia Maju: Dakwah Tasawuf Sebagai Model Moderasi Kebangsaan - Sholahuddin, Sholahuddin; Sadari, Sadari (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the da'wah of Sufism as a model of nationality in the Sustainable Development Goals for an advanced Indonesia This research is classified as qualitative with the theory plus phenomenological approach developed by Jonathan A. Smith. Data were collected through in-depth interviews, observations, and documentation involving leaders in Penajam Paser Utara. The data that has been collected is analyzed with phenomenological steps, namely: (1) reading and rereading, (2) initial noting, (3) developing emergent themes, (4) searching for connections across emergent themes, (5) moving the next cases, (6) looking for pattenrn across cases. The results showed that tasawuf da'wah also uses normative law, starting from legal materials in the form of Laws, Presidential Regulations, Regulations of the National Research and Innovation Agency (BRIN), National Research Master Plan (RIRN), and RPJMN which are in line with sustainable development goals (SDGS) for advanced Indonesia, of course with the concept of tasawuf da'wah as a model of understanding from religious moderation to national moderation with a maqasyid sharia approach and so far Indonesia is still struggling with religious moderation not yet reaching national moderation, so, the results are still repressive.